2015
DOI: 10.1118/1.4927723
|View full text |Cite
|
Sign up to set email alerts
|

Reduced dose measurement of absolute myocardial blood flow using dynamic SPECT imaging in a porcine model

Abstract: Dynamic SPECT measurement of MBF and MFR in pigs can be performed with 1/4 (Tc99m-tracers) or 1/2 (Tl-201) of the standard injected activity without significantly reducing accuracy and precision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…5). Pig studies suggest that reducing the injected activity may be possible (29), but further human studies are needed to determine the extent to which patient dose can be reduced while maintaining an accurate MBF estimate. In addition to higher noise, tetrofosmin has a lower extraction fraction at high MBF, which reduces the contrast in K 1 between normal and abnormal flow responses.…”
Section: Discussionmentioning
confidence: 99%
“…5). Pig studies suggest that reducing the injected activity may be possible (29), but further human studies are needed to determine the extent to which patient dose can be reduced while maintaining an accurate MBF estimate. In addition to higher noise, tetrofosmin has a lower extraction fraction at high MBF, which reduces the contrast in K 1 between normal and abnormal flow responses.…”
Section: Discussionmentioning
confidence: 99%
“…Our data therefore supported the utilization of CT images from a separate scan unit for SPECT only scanners as other studies have already demonstrated. 2,5 Recently some SPECT MBF study with a CZT scanner proposed to quantify MFR parameter with kinetic modeling and without physical corrections. 12 The method assumed physical errors in rest and stress scans can be similar so that they can be directly neutralized in MFR calculation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] These studies consistently demonstrated that accurate flow measurement can be achieved by either conventional dual-head SPECT/computed tomography (SPECT/CT) scanners or a new cadmium zinc telluride (CZT) SPECT scanner while dynamic SPECT (DySPECT) acquisition and full physical corrections were applicable to accurately perform kinetic modeling. [2][3][4][5] The human study further showed that absolute flow parameters can be superior to detect coronary artery disease (CAD) over perfusion abnormality scores for a patient population with high prevalence of multi-vessel CAD. 3 Consequently, the capability of SPECT MBF quantitation brought an important clinical application to enhance CAD detection for areas where flow quantitation with position emission tomography (PET) cannot be applicable due to lack of economically affordable PET flow tracers.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Good correlations of MBF (r = 0.75–0.90) compared with invasive microsphere measurements for all tracers studied and somewhat worse correlations of MFR were shown. The authors also showed recently in subsequent animal studies that low-dose SPECT flow measurements are feasible with such a solid-state camera with doses as low as one-quarter of the standard dose for 99mTc and a half dose for 201Tl [71]. Recently, human validation studies have been performed comparing fast SPECT and PET flow directly.…”
Section: Dynamic Flow With Spectmentioning
confidence: 99%